Gas flow-assisted vacuum drying: identification of a novel process for attaining high-quality perovskite films. Issue 16 (29th July 2021) - Mathies, Florian; Nandayapa, Edgar R.; Paramasivam, Gopinath; Al Rayes, Mohammad F.; Schröder, Vincent R. F.; Rehermann, Carolin; List-Kratochvil, Emil J. W.; Unger, Eva L.
Abstract : Controlling the nucleation and crystal growth in solution-processed metal halide perovskite (MHP) thin films is the pivotal point in fabricating homogenous and pinhole-free films. Abstract : Controlling the nucleation and crystal growth in solution-processed metal halide perovskite (MHP) thin films is the pivotal point in fabricating homogenous and pinhole-free films. Using scalable coating and printing techniques, vacuum and gas flow-assisted drying processes turn out to be the most promising methods to induce nucleation and crystallization. Yet, the exact interplay and nature of these processes are unclear. In our work, we optically monitor these processes in situ . For the first time, we can show that a controlled venting of the vacuum chamber and the use of a subsequent gas flow are key to achieve homogenous nucleation. Utilizing this gas flow-assisted vacuum drying process, we find that regular, optically dense and pinhole-free MHP layers can be fabricated via inkjet printing, which yield solar cells with a power conversion efficiency of 16%, as compared to 4.5% for vacuum drying.